EVALUATION OF HEPATOPROTECTIVE ACTIVITY OF ‘KARIRA’-A VALUABLE AYURVEDIC PLANT - VERMA, PREETI; PARMAR, DHARMISHTHA; SUHAGIA, BHANUBHAI (International Journal of Current Pharmaceutical Research, 2023)
Objective: ‘Karira’ is a common Sanskrit name of an important Ayurvedic medicinal plant, Capparis decidua Edgew. (family, Capparidaceae). It is a bushy shrub or small tree distributed throughout the dry areas of India and other parts of the world. As per traditional literature, various parts of the plant are widely used in the treatment of biliousness, jaundice, andas a liver tonic. Therefore the present study was aimed at the evaluation of hepatoprotective activity of Karira stem. Methods: For the study, three types of extracts of C. decidua stem were prepared, viz. aqueous extract, alcoholic extract and 50% hydroalcoholic extract. The stem extracts were evaluated for their protective effects against carbon tetrachloride-induced acute hepatotoxicity in the rats in in vivo conditions. Results: The results suggested that among all the three extracts, specifically the alcoholic extract at the dose of 300 mg/kg exhibited highest hepatoprotective activity, which was comparable to the standard drug, silymarin (50 mg/kg). The hepatoprotective effects were further confirmed by detailed antioxidant study, which revealed significant free radical scavenging activities and protection against lipid peroxidation offered by the extracts, along with preservation of the integrity of liver cells as evident from the histopathological study of the liver tissues. Conclusion: The present investigation supports the traditional use of Karira plant in liver-related disorders.